2018
DOI: 10.5937/mmeb1804087i
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the sustainable development benefits in the Serbian mining companies

Abstract: Sustainable development is the most current topic of today; it means a moderate development that meets the needs of the present generation, and does not interdict the needs of future generations. An analysis of the sustainable development benefits in the mining companies (Mining and Smelting Basin Bor, RTB) presents a problem that can be solved using the multi-criteria decisionmaking methods (MCDM). The interest in analyzing the benefits of sustainable development in the Mining and Smelter Basin Bor originated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Multi-criteria methods (MCDM) are used by managers or decision makers as the auxiliary tools in solving the real problems or deciding in different areas of economy. Recently, many MCDM methods are used, such as AHP, ELECTRE, PROMETEJ, TOPSIS, ARAS, SVARA and many others [2][3][4][5][6][7][8]). The combined MCDM methods [9,10] are also used as well as the new models [11].…”
Section: Introductionmentioning
confidence: 99%
“…Multi-criteria methods (MCDM) are used by managers or decision makers as the auxiliary tools in solving the real problems or deciding in different areas of economy. Recently, many MCDM methods are used, such as AHP, ELECTRE, PROMETEJ, TOPSIS, ARAS, SVARA and many others [2][3][4][5][6][7][8]). The combined MCDM methods [9,10] are also used as well as the new models [11].…”
Section: Introductionmentioning
confidence: 99%
“…Preloading improves the working environment increasing the load and decreasing the compressibility of soft, unbound soil. The consolidation process is accelerated by construction the vertical and horizontal drainage [1].…”
Section: Introductionmentioning
confidence: 99%
“…This method was used in the assessment of sustainable development of hard coal mining industry in Poland with a result of a total of 24 evaluation criteria in economic, environmental, and social aspects [24]. It was also used in the assessment of sustainable development benefits in the Serbian mining companies with a result of 6 evaluation criteria for 5 alternatives of sustainable production and consumption, implementation of an integrated management system, introduction of clean technology, development of social responsibility, and environmental protection [29]. In a Vietnamese study, AHP was used to measure environmental problems from titan mining with 5 alternative sites on 8 criteria [30].…”
mentioning
confidence: 99%
“…In Serbia, based on an assessment of sustainable development benefits in mining companies, it was found that the most important criterion was competitiveness, application of international standards of the efficiency, sustainable use of the natural resources, and product quality, followed by quality control of the process, reduction of costs, the introduction of new technologies, simpler procedures, and information of the employees and their participation in the decision-making process [29]. In Vietnam, RM (titan) mining most seriously affects the forests as not many forests are left along the coast.…”
mentioning
confidence: 99%